Economic consequences of international cross-listing and multimarket trading - Dodd, O (Financial Managemement Association (FMA), 2011)
This study examines the impact of cross-listing and multimarket trading on the stock’s information environment. Cross-listing is associated with additional mandatory disclosure requirements and, thus, is expected to reduce information asymmetry between management and investors and among different groups of investors. Empirical findings confirm that the quality of information environment, measured by stock liquidity and price volatility, is improved after listing on a foreign exchange. Additionally, I distinguish between cross-listing and admission to trade on a foreign exchange or cross-trading, which, in contrast to cross-listing, does not entail additional disclosure. Contrary to expectations, the difference in the impact of cross-listing and cross-trading on the stock liquidity and price volatility is not significant. This finding suggests that the improvement in the information environment of crosslisted/ traded stocks comes primarily from the intensified competition among traders rather than from mandatory disclosure requirements.
Keywords: Information asymmetry; Cross-listing; Cross-trading; Stock liquidity; Volatility